(untitled) (Research, Society and Development, 2021)
One of the main ways to protect steel against corrosion is by the galvanizing process. This process has been continuously developed and its first optimization was performed by the addition of Aluminum in the coating. As a result, Zn-5wt.%Al and 55wt.%Al-Zn coatings were developed. Recently, the search for increased corrosion resistance led to the development of zinc coating with the addition of magnesium and aluminum. In this work, a comparative study of the corrosion resistance of zinc coated steel and Zn-2wt.%Al-1wt.%Mg alloy coated steel was performed. Samples were exposed to immersion corrosion tests in 0.1 M NaCl electrolyte and were analyzed by using SEM, XDR and EIS. On zinc-coated steel, the steel substrate was attacked after 48 days of immersion, while on Zn-2wt.%Al-1wt.%Mg coated steel, the steel substrate showed corrosive process after 90-day of immersion. The corrosion product formed from Zn-2wt.%Al-1wt.%Mg coated steel is the main cause of its better corrosion resistance compared to zinc coated steel.